Community Perceptions About The Quality Of Public Services (Study On The Making Of Vehicle Number Letter At The Joint Office Of Samsat UPT. Trade Bandar District Simalungun Regency) - Yurika Meisarah Rangkuti (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2020)
This study aims to describe the public's perception of the quality of public services in the manufacture of Vehicle Registration Certificates at the UPT Samsat Joint Office. Trade in Bandar District, Simalungun Regency. Seeing public perceptions of the quality of public services is very important, because from public perceptions it can be seen how public services are provided by Samsat office employees at this time. The research method used in this study is a descriptive method that seeks to describe the phenomenon as a whole. The data were obtained by distributing questionnaires to the respondents, totaling 50 people from the City of Trade. Furthermore, the data obtained were poured into a frequency distribution table and then analyzed. Based on the results of the study the majority of respondents in the UPT Samsat Joint Office. Trafficking is male with the age of 30-39 years. The most dominant occupations of respondents are Employees and Entrepreneurs. Most of the respondents are Bataknese. From the research results obtained, the applicable requirements are in accordance with the type of service, the procedures provided are not complicated but the Samsat employees are not polite and friendly to the community and act unfairly. So it is necessary to do further research to find out what affects public services at the UPT. Trade Samsat Joint Office.